Meet the press. February 26, 2012 with David Gregory ; [produced by Betsy Fischer Martin] - Santorum, Rick, 1958-; Todd, Chuck, 1972-; Schmidt, Steve, 1970-; Parker, Kathleen; Ford, Harold, 1970-; Brewer, Janice K., 1944-; Brown, Jerry, 1938-; Martin, Betsy Fischer (Meet the press., 2012)
On this edition of Meet the Press: an interview with Rick Santorum from the campaign trail; Governors Jan Brewer and Jerry Brown discuss the issues facing the fall campaign; insights and analysis from Chuck Todd, Kathleen Parker, Steve Schmidt, and Harold Ford, Jr.